PENGARUH ARAHAN SHALAT DHUHA TERHADAP KECERDASAN EMOSIONAL SISWA SMK LABOR BINAAN FKIP UNRI PEKANBARU - Ninik Haryani; Zulfan Saam; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of research is sadly the world of education as a result of uncontrolled emotions student so with unimportant things students has done a commendable behavior. The purpose of this research is to know the level of emotional intelligence of students in school. Furthermore to know the difference in students emotional intelligence at school before and after the dhuha prayer direction. So from the difference, can know the impact of dhuha prayer direction to students' emotional intelligence in school. This research method uses Experimental Research is Pre-Experimental Designs with The One Group Pretest-Posttest. The subject of this research is 11 students selected through the pretest. Data processing has been done can be concluded is The students emotional intelligence before the direction of dhuha prayer was eleven students in the medium category. Then after given the direction of praying dhuha there are two students in the medium category, and nine students in the high category. After being given the direction to Dhuha prayer there are differences in emotional intelligence of students. The direction of praying dhuha provides a significant positive effect on students' emotional intelligence.Key Words: Emotional Intelligence, Direction of Dhuha Prayer